2021
DOI: 10.1016/j.ultsonch.2021.105615
|View full text |Cite
|
Sign up to set email alerts
|

Piezo-enhanced photocatalytic diclofenac mineralization over ZnO

Abstract: Highlights US-assisted photocatalysis by ZnO leads to efficient mineralization of diclofenac. Synergistic effects are observed only when ZnO nanorods are used. Tests in simulated water matrix show enhanced performance with respect to TiO 2 . Reaction intermediates of photo- and sonophotocatalysis are identified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 25 publications
2
29
0
Order By: Relevance
“…As reported in the literature, PANI is capable of photosensitizing TiO 2 efficiently [27], leading to the production of a large number of electron-hole pairs under visible light illumination, resulting in higher photocatalytic activity than pristine TiO 2 . In fact, it has been demonstrated that PANI modification provides an effective approach to extending the TiO 2 absorption to the visible light range, predominantly present in sunlight.…”
Section: Rhb Abatement Capacity Of Hcl-doped Pt/pusmentioning
confidence: 73%
See 2 more Smart Citations
“…As reported in the literature, PANI is capable of photosensitizing TiO 2 efficiently [27], leading to the production of a large number of electron-hole pairs under visible light illumination, resulting in higher photocatalytic activity than pristine TiO 2 . In fact, it has been demonstrated that PANI modification provides an effective approach to extending the TiO 2 absorption to the visible light range, predominantly present in sunlight.…”
Section: Rhb Abatement Capacity Of Hcl-doped Pt/pusmentioning
confidence: 73%
“…Figure S4 shows the drastic decrease in activity for both the materials. According to the literature [66], the fall of the photodegradation efficiency of the foams could be mainly attributed to the strong adsorption of the dye intermediates and products on the surface of the photocatalyst (mainly on the polymeric matrix) leading to the blockage of photocatalytic active sites (PANI/TiO2) [27], whereas losses of photocatalyst from the surface of the foam during the consecutive tests can be excluded. P/PU has low affinity towards RHB.…”
Section: Rhb Abatement Capacity Of Hcl-doped Pt/pusmentioning
confidence: 99%
See 1 more Smart Citation
“…There has been an increasing use of piezoelectric materials (either bulk solid or nanoparticles), for which mechanical activation affords charge separation through the piezoelectric effect. Clearly, ultrasonic vibration as mechanical energy has been harnessed by Meroni and associates, to activate a piezoelectric solid (ZnO), which enhances the sono-photocatalytic degradation of diclofenac, a common anti-inflammatory agent [10] . While only a slight enhancement in drug degradation was observed, a strong effect could be obtained for the mineralization process, reaching up to 70% of complete degradation.…”
Section: Overviewmentioning
confidence: 99%
“…As one of the most significant outcomes, ultrasound sonication-promoted photocatalysis (named sonophotocatalysis) has been developed using a sonication-induced piezoelectric field by suppressing the recombination of photoexcited electron–hole pairs [11] , [12] , [13] , [14] . For the emerging strategy of non-centrosymmetric sonophotocatalysts, the macroscopic spontaneous polarization field derived from the directional accumulation of polar units can facilitate the rapid separation of charge carriers and their migration from the bulk to the surface in opposite directions, inducing an increment in the catalytic capability than those of traditional photocatalysts [15] , [16] , [17] , [18] . Nevertheless, the spontaneous polarization field can be shielded by the migration of charge carriers, resulting in the loss of the driving force for carrier separation.…”
Section: Introductionmentioning
confidence: 99%